2020
DOI: 10.1155/2020/7809412
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and Factors Associated with Mortality among Children under Five Years Admitted with Severe Acute Malnutrition in the Nutritional Unit of Jinja Regional Referral Hospital, Eastern Uganda

Abstract: Background. Mortality among children with severe acute malnutrition remains an immense health concern in the hospitals in developing countries, but its attributes are not completely assessed in various hospital settings. The aim of this study was to determine the proportion of mortality, the comorbidities, and factors associated with in-hospital mortality among children under five years of age admitted with severe acute malnutrition at Jinja Regional Referral Hospital, Eastern Uganda. Methods. This was a hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Desire B et al reported malnutrition is significantly associated with mortality in less than five years children. 21 Vaccine preventable diseases are still prevalent in community as reported in current study. It suggests that immunization is still lagging behind expectations.…”
Section: Discussionmentioning
confidence: 58%
“…Desire B et al reported malnutrition is significantly associated with mortality in less than five years children. 21 Vaccine preventable diseases are still prevalent in community as reported in current study. It suggests that immunization is still lagging behind expectations.…”
Section: Discussionmentioning
confidence: 58%
“…Similar outcomes of complicated SAM were reported in Egypt, 34 in South Africa, 35 and Uganda. 36 Diarrhea was the most common comorbidity in patients at the CMAM centers. Treatment outcomes of patients without diarrhea are better than those with diarrhea.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Other factors that may be important in our setting include serving a poor pastoralist community, delayed presentation, lack of maternal participation in feeding programs, over prescription of intravenous therapies, early discontinuation of treatment due to insufficient financial means [2], and poor adherence of WHO SAM treatment guidelines [11,30]. One study from Uganda also identified WHO defined danger signs on admission, namely, lethargy, hypoglycemia, hypothermia, bradycardia, capillary refill > 2 seconds, weak pulse volume and impaired level of consciousness [12]. We did not record these clinical details nor did we collect data on biochemical indices and the socioeconomic status of caregivers.…”
Section: Plos Onementioning
confidence: 99%
“…Despite the availability of outpatient treatment, 50% of SC admitted children with SAM die due to inappropriate care [10] and one important reason is poor adherence to SAM therapeutic guidelines [11]. Other factors include the presence of danger signs seen in sicker children like lethargy, hypoglycemia and hypothermia as well as bradycardia, capillary refill > 2 seconds, weak pulse volume and impaired level of consciousness [12].…”
Section: Introductionmentioning
confidence: 99%